Ressonâncias do PIBID na formação inicial do pedagogo: o olhar das estagiárias de Capanema-PA sobre a experiência de iniciação à docência - REIS, Rosiane Gaspar (2023)
The present research was inspired by the author's participation during 18 (eighteen) months in the Institutional Program of Scholarships for Initiation to Teaching (PIBID) and had the partnership of the Elementary School Professora Maria Natividade da Silva, at the city of Capanema-PA, locus of the research. Considering the interest in understanding in what way the activities proposed in the project favored the educational path of the pedagogues participating in the research and the importance of the school as a place for learning how to teach, the object of this research is to study the educational experiences provided by PIBID during the initial formation of 7 (seven) undergraduate students of the Pedagogy course, offered by the Federal University of Pará, in the University Campus of Capanema-PA. The aim is to understand the repercussions of the experiences of initiation to teaching for the formative process of the students and for their constitution as teachers, emphasizing the most significant aspects of the experiences in the school for the learning of the profession. For the data creation, the participants of PIBID used the Final Activity Reports 2018/2020, as well as the consultations performed in the documents related to the program. In this sense, the research is based on the principles of the qualitative approach, and for the data analysis, elements of the content analysis technique were used. The results allow us to recognize the PIBID as an important initiative of a Public Educational Policy, focused on the qualification of teachers, precisely because it contains among its objectives aspects necessary for a comprehensive and meaningful initial training, for allowing an authentic articulation between theory and practice, the establishment of a collaborative partnership between university and school and the performance of basic school teachers as co-trainers of new teachers.